2021
DOI: 10.1002/ece3.8161
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and scalar variations affect resource use of northern bobwhite broods

Abstract: Disparate resource use originating from phenology of biotic resources, abiotic conditions, and life cycles of exploiting organisms underscores the importance of research across time and space to guide management practices. Our goal was to evaluate resource use of northern bobwhite (Colinus virginianus; bobwhite) at two spatial scales and across three age classes, from hatching through a period of the postjuvenile molt. Our study was conducted at Tall Timbers Research Station, Tallahassee, FL, USA—situated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 84 publications
2
4
1
Order By: Relevance
“…and reported some similar results to ours, where they observed selection for areas closer to supplemental feedlines at the third-order scale (diurnal and nocturnal). Kubečka et al (2021) failed to detect an effect of age on feedline selection, whereas we observed a positive interaction between age and distance to feedline (i.e., younger birds were more likely to occur closer to feedlines) for foraging selection. This positive interaction is opposite of our prediction that older birds would be more likely to use these areas.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…and reported some similar results to ours, where they observed selection for areas closer to supplemental feedlines at the third-order scale (diurnal and nocturnal). Kubečka et al (2021) failed to detect an effect of age on feedline selection, whereas we observed a positive interaction between age and distance to feedline (i.e., younger birds were more likely to occur closer to feedlines) for foraging selection. This positive interaction is opposite of our prediction that older birds would be more likely to use these areas.…”
Section: Discussioncontrasting
confidence: 96%
“…While there have been other studies examining the effects of supplemental feed on bobwhite resource use and movement, many have done so from Johnson's (1980) third‐ or second‐order scale; most of which were focused on suspected brooding adults (McGrath et al 2017), or brooding and non‐brooding adults (Sisson et al 2000, Buckley et al 2015, Wellendorf et al 2017). Kubečka et al (2021) were interested in the effects of supplemental feed on brood resource selection (regardless of brooding adult presence) and reported some similar results to ours, where they observed selection for areas closer to supplemental feedlines at the third‐order scale (diurnal and nocturnal). Kubečka et al (2021) failed to detect an effect of age on feedline selection, whereas we observed a positive interaction between age and distance to feedline (i.e., younger birds were more likely to occur closer to feedlines) for foraging selection.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations